Design of Roll Sheet Metal Forming Machine with Material Thickness of 0.3 mm - Bambang Hermani; Dicky Omar Muhtar (Mestro, 2022)
The role of wood as a choice of roof frames for houses is increasingly being abandoned due to high costs, wood materials are easily exposed to flying termites so that they corrode. aluminum, and zinc. So, it is more resistant to corrosion and made according to ISO standards, mild steel sheet material / metal sheet for roof truss construction is formed by profiles where the process of forming these profiles is by cold rolling, known commonly as a metal forming process or cold metal forming with external force emphasis. on the plastic condition of the steel sheet, due to the high market demand which is promising now efforts to build a light steel profile factory are springing up rapidly. The prospect of the metal forming process industry still has a good chance, therefore the initiative was taken to design a metal roll forming machine with a straight triangular groove profile with galvalume steel sheet material with a thickness of 0.3 mm and used for practical purposes in the production process. The metal forming process is a work process. metal by changing the shape of the workpiece by applying an external force so that plastic deformation occurs and the resulting mild steel profile is generally intended to be carried out at room temperature without heating the steel sheet. The design of the roll machine along with the frame to be constructed has dimensions of 200x400x275 mm and a frame of 310x400x750 mm, with the rotary wheel of the roll machine.